ISSUES OF PATHOGENESIS AND TREATMENT OF UTERINE CERVICAL DISEASES ASSOCIATED WITH PAPILLOMAVIRUS INFECTIONS - A. L. Unanyan; L. S. Sidorova; Yu. M. Kossovich; Yu. A. Rzyanina; A. E. Kadyrova (IRBIS LLC, 2016)
Uterine cervical cancer is on the 3rd place of cancerous diseases morbidity in Russia. Uterine cervical cancer is caused by persistent papillomavirus infection (PVI), therefore the main factor of uterine cervical cancer prevention is screening and vaccination against human papillomavirus (HPV). Uterine cervical cells infection with HPV is necessary, but not sufficient for their malignancy. Its important to provide adequate therapeutic measures to eliminate HIV from the organism, if infection already occurred. One of the effective methods of PVI complex conservative therapy is stimulation of cell immunity by use of natural purine analogue inosine pranobex (IP) as an immunostimulator. IP antivirus effect is associated with suppression of replication of DNA and RNA viruses by bounding to cell ribosome. Immunomodulating capacity of IP is characterized by stimulation of nonspecific immunity, enhanced interleukin production, increased antibodies synthesis, stimulation of chemotaxic and phagocytous activity of monocytes and macrophagues and polymorphonuclear cells. In present article data on open and double blind placebo-controlled studies of IP are summarized. These studies confirm IP efficacy in HPV-infection therapy.